2013
DOI: 10.1109/tasl.2012.2215594
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-Microphone Algorithm That Can Cope With Competing-Talker Scenarios

Abstract: Abstract-This paper introduces a novel technique for signal-to-noise ratio (SNR) estimation for scenarios where two closely-spaced microphones are available. The proposed technique utilizes the real and imaginary parts of the coherence function between the input signals to estimate the SNR without assuming prior knowledge of the noise statistics. The corresponding dual-microphone speech enhancement algorithm utilizes a Wiener filter as a gain function constructed using the SNR values computed by the coherence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 32 publications
(40 reference statements)
0
39
0
Order By: Relevance
“…In [8], we proposed a coherence-based dual-microphone noise reduction technique and showed that in anechoic (also low reverberant) rooms, where the noise field is highly coherent, it offers significant improvements over a fixed directional microphone and a well-established beamformer in terms of intelligibility and quality. We also observed that algorithm performance starts to degrade when tested in more reverberant rooms.…”
Section: Introductionmentioning
confidence: 99%
“…In [8], we proposed a coherence-based dual-microphone noise reduction technique and showed that in anechoic (also low reverberant) rooms, where the noise field is highly coherent, it offers significant improvements over a fixed directional microphone and a well-established beamformer in terms of intelligibility and quality. We also observed that algorithm performance starts to degrade when tested in more reverberant rooms.…”
Section: Introductionmentioning
confidence: 99%
“…The 2.2 to 7.0 dB SRT benefit of Fennec over Dipole processing in a moderately-reverberant environment (T 60 ¼ 350 ms) compares favorably to the SRT benefit for the related processing technique of Yousefian and Loizou (2013), which uses estimated input coherence to estimate the input SNR which is then processed through a Wiener filter to yield the particular time/ frequency attenuation terms [analogous to those generated by Eq. (3) for Fennec].…”
Section: Discussionmentioning
confidence: 99%
“…This approach is based on direct analysis of phase differences, rather than the use of coherence as suggested by Yousefian and Loizou (2013). This distinction can yield performance differences, particularly in more complex environments where the target speech is degraded by reverberation and by multiple, simultaneous, noise sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These assumptions, however, generally do not hold for many real situations and, therefore, these theoretical approaches provide limited practical solutions to improve beamformer performance in cochlear implant devices. Yousefian and Loizou (2013) proposed a dual-microphone coherence-based noise reduction algorithm for cochlear implant users and demonstrated 5-10 dB SRT improvement over a fixed directional microphone in an anechoic room with one or two competing talkers. The algorithm assumed that speech and noise were coherent across the microphone array, and was also evaluated by normal hearing listeners in various degrees of reverberation.…”
Section: Introductionmentioning
confidence: 99%